Peranan Parameter Antropometri dan Metabolik Terhadap Kontrol Tekanan Darah Sistolik dan Diastolik pada Kelompok Usia Produktif di Duri Kosambi - Susy Olivia Lontoh; Alexander Halim Santoso; Edwin Destra; Farell Christian Gunaidi; Kresna Bambang Fajarivaldi; Kenzie Rafif Ramadhani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Hypertension is a condition in which the pressure in the blood vessels is too high and is a significant risk factor for cardiovascular disease. This study aims to evaluate the role of metabolic and anthropometric parameters in assessing the risk of hypertension in the productive age group in Duri Kosambi. This study used a cross-sectional design with 125 respondents aged 18-59 years. Data were collected through measurements of blood pressure, hemoglobin levels, fasting blood sugar, uric acid, BMI, waist circumference, and body composition using BIA. Linear regression analysis was used to evaluate the relationship between variables. Hemoglobin levels, fasting blood sugar, waist circumference, and major body skeletal muscle mass were found to have a significant effect on systolic blood pressure. Meanwhile, fasting blood sugar and visceral fat showed a significant effect on diastolic blood pressure. Metabolic and anthropometric parameters have an important role in assessing the risk of hypertension, indicating the need for appropriate interventions to reduce the risk of hypertension and related complications. Keywords: Anthropometry, Blood Pressure, Hypertension, Metabolic, Productive Age